2011
DOI: 10.1183/09031936.00087511
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal hypoxaemia and hypercapnia in children with neuromuscular disorders

Abstract: The aim of the study was to identify daytime predictors of nocturnal gas exchange anomalies in children with neuromuscular disease (NMD) and normal daytime gas exchange.Lung function tests, respiratory muscle evaluation and nocturnal gas exchange were obtained as part of routine evaluation.We included 52 consecutive children with Duchenne muscular dystrophy (n520), spinal muscular atrophy (n510) and other NMD (n522). 20 patients had nocturnal hypoxaemia, defined as minimal arterial oxygen saturation measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 37 publications
0
44
0
7
Order By: Relevance
“…However, in a recent study performed in a group of children with NMD and normal daytime gas exchange (10 pts with SMA), Bersanini et al [33] showed that daytime lung function and respiratory muscle parameter correlate poorly with nocturnal hypoxaemia and hypercapnia reinforcing the need to routinely assess nocturnal respiratory function.…”
Section: Smamentioning
confidence: 96%
“…However, in a recent study performed in a group of children with NMD and normal daytime gas exchange (10 pts with SMA), Bersanini et al [33] showed that daytime lung function and respiratory muscle parameter correlate poorly with nocturnal hypoxaemia and hypercapnia reinforcing the need to routinely assess nocturnal respiratory function.…”
Section: Smamentioning
confidence: 96%
“…Contrairement à ces études, plusieurs études [4,9,12,14,20] n'ont pas réussi à identifier des paramètres diurnes clairement prédictifs des anomalies des échanges gazeux nocturnes et/ou des TRS. L'étude de Bersanini et al [21], qui est la seule étude à avoir comparé un nombre aussi important de paramètres diurnes (volumes pulmonaires, mécanique respiratoire, force des muscles, endurance des muscles, gaz du sang artériels diurnes) aux paramètres polysomnographiques et gazométriques nocturnes, n'a en effet retrouvé que de faibles corréla-tions, chez 52 enfants avec diverses MNM : entre la capacité vitale, la capacité résiduelle fonctionnelle, la pression maximale lors du reniflement, la pression gastrique à la toux et l'hypoxémie nocturne ; entre la PaCO 2 diurne, le pH diurne et l'hypercapnie nocturne ; ou entre la PaCO 2 diurne et l'IAH.…”
Section: Relation Entre Trs Et Fonction Respiratoire-muscles Respiratunclassified
“…En dehors de l'asthme qui représente 80 % de la pathologie explorée dans la majorité des laboratoires, d'autres pathologies peuvent également bénéficier d'une exploration dans le cadre de leur suivi [33][34][35][36][37][38][39].…”
Section: En Gazométrie Cutanéeunclassified
“…Certaines pathologies respiratoires ne surviennent que pendant le sommeil, comme le syndrome d'apnée obstructive du sommeil (SAOS) dont l'hypertrophie amygdalienne est la cause la plus fréquente chez l'enfant [35,[56][57][58][59][60].…”
Section: Sur Le Plan Respiratoireunclassified